Nutritional State of Schools of Antioquia and Quindío : Epidemiological Alert for Colombia (2020)
ABSTRACT: Introduction: Obesity is considered a serious public health problem, associated with the development of chronic non-communicable diseases. Serving the overweight school population is an imperative, since weight gain during this stage conditions excess weight in adulthood. Objectives: To analyze the nutritional status of the school population of the city of Medellín and the city of Armenia, Colombia Methods: Two elementary and high school basic education institutions were selected from the cities of Medellín and Armenia. Anthropometric measurements (weight, height, age, and sex) were collected, and BMI was classified according to age, using the Anthro Plus program and the SPSS. Verification of data collection was carried out, anthropometrically reassessing 10% of the population already nutritionally classified, in addition, expert validation of the BMI classification according to age was carried out. Results: 593 schoolchildren were evaluated, 416 in Medellín and 177 in Armenia. In Medellín, 53.1% presented adequate nutritional status, 37.8% excess weight; (25.5% overweight and 12.3% obesity), 9.1% weight deficit, (7.9% risk of thinness and 1.2% in thinness); the greater obesity in men. In Armenia, 33.5% were overweight (20.6 overweight and 12.9% obese), 9.1% weight deficit (7.6% risk of thinness and 1.8% thinness) and 57, 1% adequacy. Conclusions: The obesity level was found similar in both cities, but the overweight level was higher in Medellín. According to the National Survey of the Nutritional situation -ENSIN- 2015, the excess weight index for Colombia was 24.4% for this population group, which indicates that, four years later, in 2019 in Medellín, the national average of excess in 54.9%, and in Armenia in 37.3%, with the aggravating circumstance that at the age of 11 years, it exceeds 100% of the national average in Medellín, with 51% of schoolchildren with excess of weight, generating an alert at the national level to identify its determining factors and generate relevant interventions.